2015
DOI: 10.1007/s11356-015-5164-5
|View full text |Cite
|
Sign up to set email alerts
|

Environmental microbiology as a mosaic of explored ecosystems and issues

Abstract: Microbes are phylogenetically (Archaea, Bacteria, Eukarya, and viruses) and functionally diverse. They colonize highly varied environments and rapidly respond to and evolve as a response to local and global environmental changes, including those induced by pollutants resulting from human activities. This review exemplifies the Microbial Ecology EC2CO consortium's efforts to explore the biology, ecology, diversity, and roles of microbes in aquatic and continental ecosystems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 130 publications
(113 reference statements)
0
5
0
Order By: Relevance
“…In contrast, the rocks found at the Agriculture, Capingui Outlet, Marau Grain, and Marau Animal sample sites had significantly less biofilm biomass (Table 2) have repercussions on the quantity and functioning of biofilms and even on ecosystem processes (Bier et al, 2015;Faure et al, 2015;Zhang et al, 2015;Battin et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…In contrast, the rocks found at the Agriculture, Capingui Outlet, Marau Grain, and Marau Animal sample sites had significantly less biofilm biomass (Table 2) have repercussions on the quantity and functioning of biofilms and even on ecosystem processes (Bier et al, 2015;Faure et al, 2015;Zhang et al, 2015;Battin et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…In recent times, the integrative studies of microbial interactions are exploring the diversity and complexity of bacterial relationships (which included microbial signal transduction and sensing) at various levels (cellular, population, community, or even at the holobiont level) (Faure et al 2015). (Lüttge and Scarano 2004) reported that ecophysiological performance varied largely at intra-specific level in time and space, often (but not always) at inter-species level, ecophysiological performance was related to species dominance in the community.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of isolates from saltern sample may be due to the hygiene standards that are maintained for salterns or due to prevalent extreme environmental conditions. Many isolates, although being low abundance that dominated the community in an intertidal zone either appeared occasionally or persisted at low frequencies, functioning as a seed bank (Faure et al 2015).…”
Section: Isolation and Identification Of Isolatesmentioning
confidence: 99%
“…Both chemical and microbial pollutants reach surface waters via point sources (such as urban sewage) or diffuse sources (linked to runoff) of pollution. It is well known that during rainfall events, particles from terrestrial soils and river basin sediments remobilize, and affect water quality (Garcia-Esteves et al 2007;Dumas et al 2015;Faure et al 2015) because soils and sediments store pathogens, nutrients and pollutants. Thus, suspended particles have a crucial role in the transfer of contaminants to surface waters through runoff and in the resuspension of river sediments during storms (Turner and Millward 2002;Amalfitano et al 2017).…”
Section: Introductionmentioning
confidence: 99%